2018
DOI: 10.1080/24732850.2018.1466260
|View full text |Cite
|
Sign up to set email alerts
|

Staff Perceptions of Facilitators and Barriers to the Use of a Short- Term Risk Assessment Instrument in Forensic Psychiatry

Abstract: Prospective adverse events within forensic settings should be assessed using structured risk assessment instruments. Our aim was to identify the barriers and facilitators of a structured instrument for assessment of short-term risk within inpatient forensic psychiatric care. The instrument was piloted at a forensic psychiatric clinic. Three focus group interviews were conducted with staff. Content analysis revealed three main categories of barriers and facilitators for clinical use: implementation object, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Collaborative risk assessment and management have been recommended in health policy for over a decade in the UK ( 48 ). However, there is evidence that the extent to which patients are involved in risk assessment is suboptimal ( 49 , 50 ). Patients are often not aware of the content of their risk assessments let alone included in their development ( 51 ).…”
Section: Collaborative Risk Assessment and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaborative risk assessment and management have been recommended in health policy for over a decade in the UK ( 48 ). However, there is evidence that the extent to which patients are involved in risk assessment is suboptimal ( 49 , 50 ). Patients are often not aware of the content of their risk assessments let alone included in their development ( 51 ).…”
Section: Collaborative Risk Assessment and Managementmentioning
confidence: 99%
“…Collaborative risk assessment and management may also lead to patients taking increased accountability for their own recovery ( 60 ), and providing information on their internal mental states which are associated with risk ( 61 ). However, the research which has been conducted indicates that the extent to which collaborative risk assessment is occurring may be suboptimal ( 49 , 50 ). However, evidence of the value of collaborative care in evaluating risk in secure and forensic settings does exist, and remains a possible means of improving forensic care ( 62 ).…”
Section: Collaborative Risk Assessment and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this did not always happen (Gilbert et al, 2011; Woods, 2013). Staff tentatively suggested that the START had been used to inform decisions about risk management (Levin et al, 2018). Survey results indicated that one third of nurses agreed that an emphasis on the importance of risk assessment inherently reinforces risk averse practices, while slightly more, two in five, disagreed (Downes et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Risk assessment instruments can improve clinical decisions, increase transparency in decision making, and enhance communication within the health-care team (Levin et al, 2018). Although they are better at predicting the risk of violence than unstructured clinical judgement (Fazel et al, 2012), their use remains ethically complex, notably because they still cannot predict future acts of violence very well (Douglas et al, 2017).…”
Section: Risk and Its Assessmentmentioning
confidence: 99%